1,8-Diazabicyclo[5.4.0]undec-7-ene (DBU): a highly efficient catalyst in glycerol carbonate synthesis - Munshi, Mudassir K.; Gade, Swapna M.; Mane, Manoj V.; Mishra, Deepti; Pal, Sourav; Vanka, Kumar; Rane, Vilas H.; Kelkar, Ashutosh A. (Journal of Molecular Catalysis A-Chemical, 2014)
Transesterification of dimethyl carbonate (DMC) with glycerol (GLY) was investigated using various amines as catalysts. Amidines like 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) and 1,5-diazabicyclo[4.3.0]non-5-ene (DBN) were found to be the best catalysts for this reaction. Best results: 98% conversion of GLY with 96% selectivity to GC (TON: 9408), were obtained with DBU as a catalyst. Effect of various reaction conditions on activity and selectivity were investigated using DBU as catalyst. The mechanism of the reaction was investigated with the help of H-1, C-13 and N-15 NMR analysis and OFT calculations. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: DBU; Glycerol; Glycerol carbonate; transesterification